D. Geraint James Lecture: The sarcoidosis saga: what insights from the past will guide us in the future - Baughman, Robert P.; Lower, Elyse (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
The sarcoidosis community in general and the World Association of Sarcoidosis and Other Granulomatous diseases (WASOG) in particular have led efforts to improve sarcoidosis diagnosis and care. Evidence based guidelines regarding the diagnosis and treatment have recently been published. In addition, several clinical trials examining existing and new treatments for sarcoidosis have been completed and published. In addition, WASOG has developed criteria and identified Centers of Excellence for sarcoidosis care around the world. In discussing what insights from the past will guide us in the future, this paper focuses on three specific topics: updating the diagnosis of sarcoidosis, using placebo-controlled trials to illuminate the natural course of pulmonary sarcoidosis; and exploring multidisciplinary sarcoidosis clinic care using Centers of Excellence. New approaches for diagnosis of sarcoidosis and steroid tapering are proposed based on current literature.